Implementasi Pembelajaran Kitab Ta'limul Muta'allim Dalam Membentuk Karakter Santri Madrasah Diniyah Hidayatul Mubtadiin Lampung Selatan - Faturrahman Faturrahman; Muhammad Feri Fernadi; Nurwinda Apriyani (Departement of Mathematics Education, 2023)
This exploration plans to dissect the execution of learning the book Ta'limul Muta'allim in shaping understudy character at Madarasah Diniyah Hidayatul Mubtadiin. What are the snags confronted and the arrangements in executing the learning of the Ta'limul Muta'allim This sort of examination utilizes a subjective distinct methodology with a naturalistic worldview. Information hotspot for getting a picture of gaining from the Book of Ta'lim Muta'allim. Information was acquired utilizing perception, meetings and documentation strategies. All information is examined intelligently and constantly, including decrease, information show and check. The consequences of the exploration show that: The execution of learning the book Ta'limul Muta'allim at Madarasah Diniyah Hidayatul Mubtadiin South Lampung was completed utilizing a means of understanding books, deciphering gandul, retaining nadhoman from the book. In particular, the ethical book Ta'limul Muta'allim is connected with the ethics of understudies, so from this learning understudies are expected to peruse and comprehend after that they are likewise expected to apply instances of good ethics contained in the book Ta'lim Al-Muta'allim . The association with character arrangement is that from the material educated in regards to a few ethics in this material, understudies are expected to act pleasantly in the wake of giving guidelines in regards to material that has been instructed or that has not been conveyed, so the soul of good upright person is imbued. The hindrance confronted and the arrangement in executing the investigation of the book Ta'limul Muta'allim in molding the personality of understudies at Madarasah Diniyah Hidayatul Mubtadi in South Lampung is that there are as yet numerous understudies who can't dominate Javanese. The answer for the obstructions confronted is that the ustadz involves two dialects in his conveyance, specifically utilizing Javanese and afterward making sense of it with data utilizing Indonesian, so he can proceed to exist and keep up with the information on the salaf.